2016
DOI: 10.1038/bjc.2016.231
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal hormone therapy and breast cancer: what is the true size of the increased risk?

Abstract: Background:Menopausal hormone therapy (MHT) increases breast cancer risk; however, most cohort studies omit MHT use after enrolment and many infer menopausal age.Methods:We used information from serial questionnaires from the UK Generations Study cohort to estimate hazard ratios (HRs) for breast cancer among post-menopausal women with known menopausal age, and examined biases induced when not updating data on MHT use and including women with inferred menopausal age.Results:Among women recruited in 2003–2009, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 52 publications
(149 reference statements)
3
38
1
2
Order By: Relevance
“…Nonetheless, findings from our study are consistent with those from previous studies which indicate a greater risk of breast cancer among HRT users than non-users (34–36). Unlike the Collaborative Group on Hormonal Factors in Breast Cancer study and more recent studies (34,37,38), which have reported that longer duration of HRT use is associated with increased risk of breast, we did not observe any association between duration of use and breast cancer. Nonetheless, the positive association observed in this study between HRT use and breast cancer risk is in accord with biologically plausible evidence which suggests that hormones such as estrogen may induce breast carcinogenesis by promoting tumor cell proliferation and migration (3941).…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, findings from our study are consistent with those from previous studies which indicate a greater risk of breast cancer among HRT users than non-users (34–36). Unlike the Collaborative Group on Hormonal Factors in Breast Cancer study and more recent studies (34,37,38), which have reported that longer duration of HRT use is associated with increased risk of breast, we did not observe any association between duration of use and breast cancer. Nonetheless, the positive association observed in this study between HRT use and breast cancer risk is in accord with biologically plausible evidence which suggests that hormones such as estrogen may induce breast carcinogenesis by promoting tumor cell proliferation and migration (3941).…”
Section: Discussioncontrasting
confidence: 99%
“…10 As shown with other studies, there was no increased risk of breast cancer seen for users of oestrogen-only therapy.…”
Section: Best Practice For Hrtsupporting
confidence: 51%
“…The Hazard Ratio for oestrogen-only HRT was not increased (HR=1.00; 95% CI: 0.66-1.54). 13 In our study, none of the patients had ever taken menopausal hormone replacement therapy.…”
Section: Discussionmentioning
confidence: 70%